(untitled) (PERcursos Linguísticos, 2021)
This article intends to introduce a panorama of activities developed at an Application High School from Minas Gerais, enabled by PIBID (Institutional Teaching Initiation Scholarship Program), as well the reflections and learnings provided by them. Having as theoretical basis the discussions of Oliveira (2017), Ferreira (2005), Kunz et al. (2011), among others, three performance perspectives are presented: the first one approaches Literature, specifically, poetry; the second one is a work developed with the genre textual chronic; the third one exhibits the dynamic of an rotation scheme between the classes. The work intends to publicize the nature of these actions, the multiple strengths for the school, the students, the teachers and for us, the Project participants, emphasizing the construction of our teaching identity. For that, the article discusses the operation context, the need to adapt to students’ difficulties and the work with Textual Genres and Literature.